Social responsible practices in Portuguese SME’s - Gabriel, Carla (2019)
This research examines what social responsible practices Portuguese SME implements, identifying different company profiles. Data collection was based on a questionnaire. The cluster analysis revealed four groups of companies representing four different implementation levels of social responsibility practices: low; medium-low; medium-high; and high CSR implementation. Companies revealing higher levels of CSR practices tend to be larger, older, with a higher turnover value and with some type of certification.